Virtual Lucidity: A Media Archaeology of Dream Hacking Wearables - Aleena Chia (ScholarWorks @ UMass Amherst, 2019)
In 2014, engineers and entrepreneurs began meeting up in San Francisco to explore how virtual reality and lucid dreaming headsets using electroencephalography and other kinds of biofeedback could stimulate altered mental states. They called these practices “consciousness hacking” and referred to research, financing, and design efforts around these wearables as a movement. Unlike Quantified Self practitioners who combine bodily self-tracking and population analytics to optimize health and productivity, these hackers prod their bodies to gain immediacy to their consciousness. By turning perception inward, they attempt to displace the mediation of technologies. They believe hacking the mind through data-driven stimulation can transform it into the ultimate medium for purposeful dreams, flow states, positive emotions, and secular revelations about the self, unconscious, and nature of experience. How do these practices reconcile New Age assumptions about the sacred essence of the self, with biopolitical assumptions about the self as a database to be rationalized according to the 24/7 demands of late capitalism? This essay uses media archeology to examine how discursive and material practices around consciousness hacking proffer a vision about the mind as medium that is futuristic yet ancient. By using the Consciousness Hacking movement as a starting point to investigate historical neuro-stimulative apparatuses for lucid dreaming, media archaeology can trace convergent trajectories of self-knowledge and self-making. This analysis traces connections from Bert Kaplan’s 1950s database of dreams, to crowdfunded EEG headsets that promise to unlock the secrets of the collective unconscious using big data analytics. By probing historical antecedents of datalogical fantasies, this project demonstrates the value of critical inquiry into the techno-spiritual undercurrent of contemporary technoculture, its models and mechanisms for the human sensorium, and its metaphors that we live by.